Cloning and Expression of the Neuropeptide F and Neuropeptide F Receptor Genes and Their Regulation of Food Intake in the Chinese White Pine Beetle Dendroctonus armandi - Liu, Bin; Fu, Danyang; Gao, Haiming; Ning, Hang; Sun, Yaya; Chen, Hui; Tang, Ming (Frontiers in Physiology, 2021)
The neuropeptide F (NPF) is an important signaling molecule that acts as a neuromodulator to mediate a diversity of physiological functions and behavioral processes from vertebrates to invertebrates, by interaction with NPF receptors, which are a kind of G protein-coupled receptor (GPCR). However, there are no reports on the functional roles of NPF in Chinese white pine beetle, Dendroctonus armandi Tsai & Li , (Coleoptera: Curculionidae, Scolytinae). We have cloned and characterized one NPF and two NPFR genes in the D. armandi and made bioinformatics predictions according to the deduced amino acid sequences. And they were highly similar to that of Dendroctonus ponderosa. The transcription levels of these genes were different between larvae and adults of sexes, and there were significant differences among the different developmental stages, tissues, and between beetles were under starvation and following re-feeding states. Additionally, downregulation of NPF and NPFR by injecting dsRNA into beetles reduced their food intake, caused the increases of mortality and decreases of body weight, and also resulted in a decrease of glycogen and free fatty acid and an increase of trehalose. These results indicate NPF signaling pathway plays a significant positive role in the regulation of food intake and provides a potential target for the sustainable management of this pest.